The Public Mapping Project How Public Participation Can Revolutionize Redistricting - McDonald, Michael P. (Brown Democracy Medal, 2018)
The Laurence and Lynne Brown Democracy Medal is an initiative of the McCourtney Institute for Democracy at Pennsylvania State University. It annually recognizes outstanding individuals, groups, and organizations that produce exceptional innovations to further democracy in the United States or around the world. Micah Altman and Michael P. McDonald unveil the Public Mapping Project, which developed DistrictBuilder, an open-source software redistricting application designed to give the public transparent, accessible, and easy-to-use online mapping tools. As they show, the goal is for all citizens to have access to the same information that legislators use when drawing congressional maps-and use that data to create maps of their own. Thanks to generous funding from The Pennsylvania State University, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.